EFFECTIVENESS OF SOCIAL MEDIA MARKETING AND E-SERVICE QUALITY ON REPURCHASE INTENTION THROUGH BRAND LOYALTY - Wahyuningtiyas, Nanik; Ramadhan, Tri Sugiarti (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This study aims to analyze and explain (1) determine the influence of Social Media Marketing on Brand Loyalty; (2) determine the effect of Social Media Marketing on Repurchase Intention; (3) determine the effect of E-Service Quality on Brand Loyalty; (4) determine the effect of E-Service Quality on Repurchase Intention; (5) determine the effect of Brand Loyalty on Repurchase Intention; (6) determine the influence, Social Media Marketing and e-Service Quality on Repurchase Intention through Brand Loyalty. Design/methodology/approach: This study used a data collection method with questionnaires with a quantitative approach. The population that is the object of research is OVO application users, with as many as 165 respondents—analysis testing using SEM with Smart PLS software. Findings: Based on the analysis of the research results, the following conclusions were obtained, Social media marketing has a significant effect on brand loyalty, Social media marketing has a significant impact on repurchase intention, E-Service quality has a considerable effect on brand loyalty, E-service Quality does not have a significant impact on repurchase intention, Brand loyalty has a significant effect on repurchase intention, Social media marketing and electronic service quality has a significant impact on purchase intent through brand loyalty. Research limitations/implications: Because of the distribution of questionnaires through google forms, the results obtained are less in-depth; it is recommended that further research can add other variables and use more in-depth measuring devices so that results are close to the real thing. Practical implications: The results of this research can be used by digital wallet service providers to improve e-service quality further if they want to get loyal consumers and continue to use it repeatedly. Originality/value: This Paper is Original. Paper type: Research paper Keywords: Social Media Marketing, E-Service Quality, Brand Loyalty, Repurchase Intention.